Human Cutaneous Anthrax, Georgia 2010–2012 - Kracalik, Ian (Centers for Disease Control and Prevention, 2014)
We assessed the occurrence of human cutaneous anthrax in Georgia during 2010–-2012 by examining demographic and spatial characteristics of reported cases. Reporting increased substantially, as did clustering of cases near urban centers. Control efforts, including education about anthrax and livestock vaccination, can be directed at areas of high risk.